Markets on the edge: Beach kiosk TripAdvisor consumer online reviews as dataset to compare Australian and Brazilian beachfront collective representations - Marina de Souza Sartore; Brian Coffey (Política & Sociedade)
Consumer online reviews are written by amateurs, are published very fast, and are freely accessible by anyone having internet access, bringing analytical challenges to the Social Sciences. In this exploratory paper, we compare Australian and Brazilian beach kiosk TripAdvisor Written Reviews (TWRs) and argue that they are a useful source to perceive differences in beachfront collective representations. We also argue that to better understand the socio-logics of beachfront collective representations, the content analysis of TWRs alone can be limited; therefore, we draw on other qualitative methods, such as document analysis and field observation. By combining such methods, we conclude that Australian and Brazilian beachfront collective representations differ in categories of time and space. Understanding beachfront collective representations of different countries can bring consistent knowledge to help politicians tackle current coastal challenges, especially the balance between commercial development and natural conservation of the beachfront.